FEATURES OF COMMUNICATIVE INTERACTION OF PILOTS IN THE PROCESS OF SOLUTION OF PROBLEM SITUATIONS AS COMPONENT OF PROFESSIONAL READINESS - Задкова, О. В.; Бродова, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The topical problems of professional training of the civil aviation flight team ensuring flight safety are covered in this article. The aviation accidents statistics indicate that the vast majority of them are caused by a human factor. Modern aviation engineering capabilities determine the necessity of optimization of the aviation personnel training. Since the level of flight team training is one of the key indicators of reliable operation of the air and transport system. However, the key problem associated with the human factor is the problem of readiness of the airman for professional activity including the reliability of knowledge, skills and abilities in normal and extreme conditions. There has been presented the concept of the structure of professional readiness of a pilot that includes nine blocks. There has been clarified the concept of readiness of future pilots for solving problem situations. The article also considers the peculiarities of the professional activity of the flight team. There has been specified the importance of preparing future pilots for activity in special flight situations. At the same time, there has been emphasized the interaction between crew members meaning the well-directed formation of communicative skills of pilots for effective communication during aircrafts flight operation. There has been given the definition of ‘future pilots communicative skills’. There has been determined the place of communicative skills of pilots and readiness for solving problem situations in the process of professional activity within the structure of professional readiness of a pilot. It has been noted that such communicative traits of a pilot, as the ability to get on well with people, tactfulness, outspokenness, good verbal abilities, etc. fall into the social and psychological profile, as well as heuristic components of the activity related to readiness of solving problem situations that may occur during the aircraft flight operation. The authors have stated the objective of the flight team professional training as a set of specially-used effective forms and means of teaching communication.